P148. Timing of post-training transcranial direct current stimulation to enhance consolidation of motor sequence learning in older people. Issue 8 (August 2015) - Rumpf, J.-J.; Hinselmann, K.; Fricke, C.; Weise, D.; Classen, J.
<x xml:space="preserve">Abstract</x> Objective Consolidation, by which performance improvements following a training intervention are secured and sometimes generated, is reduced in older adults and may thus represent an attractive therapeutic target. In a previous study (Rumpf et al., in preparation), we found that anodal transcranial direct current stimulation (tDCS) applied to the primary motor cortex (M1) immediately after a training session enhances consolidation of motor sequence learning in healthy older adults. The current study was designed to further investigate the effective time window of post-training tDCS with regards to consolidation. Methods 45 healthy elderly subjects (mean age 67.3 y, 27 female) were included. All participants performed a training session (14 blocks) of an explicit motor sequence learning task at 11 a.m. and were retested (4 blocks) 8 h later (7 p.m.) to assess offline-consolidation. Subjects were instructed to perform a five element sequence with their right hand as fast and accurate as possible. Each block was terminated after 60 movements. Therefore, a maximum of 12 correct sequences could be executed within one practice block. After training, all participants took part in 3 stimulation sessions. Verum anodal tDCS to left M1 was applied immediately after training (Stim0 group, n = 12), 60 min (Stim60 group, n = 11) or 120 min after training (Stim120 group, n = 11), while sham tDCS was administered during the two other stimulation sessions. The sham group (SHAM, n = 11) received sham tDCS in all three sessions. Speed (average time to complete a correct sequence per block, TCS) and accuracy (errors per block) measures were used to calculate a Performance Index (PI = exp−(TCS) ∗ exp−(errors/12) ∗ 100). Results To assess consolidation of motor sequence learning, retest performance (PI) was normalized to the end of training performance (EoT, last 3 training blocks), when asymptotic performance was reached. One-way ANOVA comparing the retest performance (mean normalized PI of the four retest blocks) revealed a significant difference between groups (F(3, 44) = 3.062, p = 0.039). Post hoc t-tests show that this effect was driven by the improved performance of the Stim0 group relative to the other groups (Stim0 vs. SHAM: p = 0.021, Stim0 vs. Stim60: p = 0.041, Stim0 vs. Stim120: p = 0.01). No statistically significant differences between the SHAM, Stim60 and Stim120 groups were found. Within group, only Stim0 group showed significant retest improvements compared to EoT baseline (p = 0.021; SHAM, p = 0.99; Stim60, p = 0.60; Stim120, p = 0.68). Conclusions These results suggest that post training application of anodal tDCS effectively enhances off line consolidation in older adults by interaction with early post-training processes in M1.